IL-7–dependent and –independent lineages of IL-7R–dependent human T cells - Arango-Franco, Carlos A.; Ogishi, Masato; Unger, Susanne; Delmonte, Ottavia M.; Orrego, Julio César; Yatim, Ahmad; Velasquez-Lopera, Margarita M.; Zea-Vera, Andrés F.; Bohlen, Jonathan; Chbihi, Marwa; Fayand, Antoine; Sánchez, Juan Pablo; et al. (The Journal of Clinical Investigation, 2024)
Infants with biallelic IL7R loss-of-function variants have severe combined immune deficiency (SCID) characterized by the absence of autologous T lymphocytes, but normal counts of circulating B and NK cells (T–B+NK+ SCID). We report 6 adults (aged 22 to 59 years) from 4 kindreds and 3 ancestries (Colombian, Israeli Arab, Japanese) carrying homozygous IL7 loss-of-function variants resulting in combined immunodeficiency (CID). Deep immunophenotyping revealed relatively normal counts and/or proportions of myeloid, B, NK, and innate lymphoid cells. By contrast, the patients had profound T cell lymphopenia, with low proportions of innate-like adaptive mucosal-associated invariant T and invariant NK T cells. They also had low blood counts of T cell receptor (TCR) excision circles, recent thymic emigrant T cells and naive CD4+ T cells, and low overall TCR repertoire diversity, collectively indicating impaired thymic output. The proportions of effector memory CD4+ and CD8+ T cells were high, indicating IL-7–independent homeostatic T cell proliferation in the periphery. Intriguingly, the proportions of other T cell subsets, including TCRγδ+ T cells and some TCRαβ+ T cell subsets (including Th1, Tfh, and Treg) were little affected. Peripheral CD4+ T cells displayed poor proliferation, but normal cytokine production upon stimulation with mitogens in vitro. Thus, inherited IL-7 deficiency impairs T cell development less severely and in a more subset-specific manner than IL-7R deficiency. These findings suggest that another IL-7R–binding cytokine, possibly thymic stromal lymphopoietin, governs an IL-7–independent pathway of human T cell development.